TED HUGHES, ECOSPHERIC VISION AND THE ROMANTICS: A REAPPRAISAL OF THE ROLE OF A POET - Dhariwal, Jaibir; Parashar, Rajbir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ted Hughes’ early poetry demonstrates a profound engagement with nature, foregrounding his ecospheric imagination—a worldview that integrates human and non-human realms. This paper explores how his poetic vision aligns with Romantic traditions, especially those of Wordsworth and Coleridge, while simultaneously breaking new grounds in representing ecological interconnectedness. His early works, such as The Hawk in the Rain, Lupercal and Wodwo, reveal an intense fascination with the raw vitality of nature, embodying an ethos that recognizes the intrinsic value and agency of the non-human world. By drawing on some key aspects of Romantic poetry, Hughes extends Romantic role of a poet and his/her preoccupation with the sublime, the pastoral, and the natural world. He reinterprets their worldview of natural world with a fresh emphasis and vision of poet and poetry. The study highlights how Hughes’s role as a poet emerges from the historical and literary experiences of later half of twentieth century and ecospheric ethics. However, this happens with certain definite continuities with different poetic practices among the Romantics. The research paper examines his innovative use of imaginative and symbolic resources of romantic sensibility, language and imagery to articulate an urgent ecospheric vision. This is also an attempt to establish that without his roots in the creative practice and vision of the Romantic tradition, Ted Hughes would have been a different kind of poet. By revisiting Hughes’s poetic beginnings, this paper underscores his role as a pivotal figure in literary articulation of ecological awareness carrying forward basics of his literary predecessors in 19th century. It involves intermittent references to his early works, both reflections in prose and poetry.